The buccaneers [videorecording (DVD)] - Saville, Philip; Gugino, Carla, 1971-; Sorvino, Mira; Elliott, Alison, 1970-; Wharton, Edith, 1862-1937 (BBC Video ; Distributed by Warner Home Video, 2006)
Four young American girls journey from America to England in search of romance and adventure in this exquisite production of Edith Wharton's final book.